PENJADWALAN DAN PEMBERIAN PAKAN IKAN OTOMATIS BERBASIS INTERNET OF THING MENGGUNAKAN NODEMCU ESP8266 DAN APLIKASI BLYNK STUDI KASUS : TOKO FISH FRIENDLY - COMPUTING INFORMATIKA; yaya suharya; Nurul Imamah (COMPUTING | Jurnal Informatika, 2023)
The utilization of the Internet of Things (IOT) in everyday life has penetrated into various fields, including in the field of animal husbandry. In this study, the authors raised a problem found in the Fish Friendly fish shop as a research site. The main problem found in this study is that farmers have difficulty in feeding which is carried out regularly and on a schedule. Sometimes in certain conditions, farmers cannot feed fish according to their schedule, this can cause a decrease in the quality of fish health so that it has a negative impact on the selling price of fish. This factor can be very important considering that fish feed must be maintained in quality and quantity. Based on the existing problems, a solution was created to design and make a tool by utilizing an automation system using IoT (Internet of things). To get the complete data needed, the author uses interview and field observation methods, besides that this research uses NodeMCU ESP8266 microcontroller devices and Servo Motors to design automatic feeders, as well as the use of the Blynk application as a remote control via a smartphone. The result of this study is that the tool made can provide feed to fish according to a predetermined schedule so that feeding can work periodically and effectively. In addition, remote control carried out through the blynk application runs smoothly, so the tool can work without manual control anymore.